Outcomes of Re-feeding Older Adolescents and Adults with Eating Disorders - Salter, Fiona (Curtin University, 2024)
This thesis reports on the physical and psychological outcomes of a high-energy feeding protocol used for nutritional rehabilitation of older adolescents and adults with eating disorders (ED) in a specialist inpatient ED treatment program. The prospective observational study of ninety-seven participants demonstrated positive weight and psychological change with minimal adverse events. Compared to existing research, this study provides a broader evaluation of inpatient treatment which will guide clinicians and researchers on safe, effective ED care.